LEGAL REGULATION OF SOCIAL PROTECTION OF INTERNALLY DISPLACED PERSONS: PROBLEMS AND SOLUTIONS - Alimova , I. (Theory and Practice of Public Administration, 2020)
The article presents conceptual approaches in the field of legal regulation of social protection of internally displaced persons.The analysis of the main legal acts regulating social protection of the citizens of Ukraine showed that the norms of the mentioned laws are especially topical in the conditions of internal resettlement for the specified category of the population.A law establishing guarantees of respect for the rights, freedoms and legal interests of internally displaced persons is considered, as well as a law under which pensions are paid to residents of temporarily occupied territories.The imperfection of the existing legislative framework for ensuring the constitutional rights and guarantees of respect for the rights and freedoms of internally displaced persons has been fully revealed.The publication deals with the peculiarities and needs of social protection of internally displaced persons and the necessity for special approaches to the legal regulation of this category of citizens. The State Migration Policy Strategy for the period up to 2025 requires additional regulation at the state level, which will determine the legal status of internally displaced persons and the specifics of their social protection.Attention is drawn to the necessity for the development and approval by the Ministry of Social Policy the Concept of social protection of children, who have been displaced from the temporarily occupied or annexed territories of Ukraine.The legal regulation of social protection of internally displaced persons is accompanied by several unresolved issues, including the organization of children’s health and recreation, the maintenance of a network of children’s health facilities. Therefore, the ways to solve them need immediate implementation, based on the urgency and depth of the problems that currently exist in Ukrainian society.Conclusions of the research and prospects for further studies. Therefore, the issue of social protection for internally displaced persons in Ukraine has a significant legal basis, but it should be noted sufficiently general that it applies not only to the category of internal migrants but also to all categories of Ukrainian citizens. To identify and find ways to address the problems of internal migrants and their children, the regulatory framework on this issue requires significant expansion, refinement and improvement.There are a wide range of issues that need urgent solution, in particular, the regulation of the legal status of internally displaced persons in the legal framework of Ukraine, the definition of the main directions of state migration policy in the context of social protection of this category of citizens, the development of ways of adaptation and psychological assistance to children of IDPs. Accordingly, new legislation and existing legislations need to be adopted and improved, which will improve the social protection of internally displaced persons.The prospect of further research in this area is to study the problems and prospects of forming an effective model of social protection for internally displaced persons